Prevalence of urinary incontinence in Brazilian para athletes - Barbosa, P. N.; Rodrigues, M. P.; Silva, A. A. C.; Lemos, C. I. L.; Silva, M. P. M. (British Journal of Sports Medicine, 2024)
Objective To describe the prevalence of urinary incontinence (UI) in para athletes in Brazil.